Answer:
- x = 33
- Indicated angles: 126°
Explanation:
We can tell that 4x - 6 is equal to 2x + 60 because they are vertically opposite angles. Now, let's solve.
- => 4x - 6 = 2x + 60
- => 4x - 2x = 6 + 60
- => 2x = 66
- => x = 33
Since we have found the required variable, we can now solve the indicated variables.
Given angles:
Let's solve 4(33) - 6 first.
Therefore, 4(33) - 6 measures about 126°. Now, let's solve 2(33) + 60.
We can clearly see that both angles are equal (126 = 126) Because of vertically opposite angles.
Conclusion:
Therefore, the required variable is 'x = 33' and when we substitute the variable in both angles, we find that both angles show 126°.
Hoped this helped.